E-Cigarette Awareness, Perceptions and Use among Community-Recruited Smokers in Hong Kong - Wang, Man Ping (PLoS One, 2015)
BACKGROUND: Electronic cigarettes (e-cigarettes) are being increasingly used. We examined the correlates associated with e-cigarette awareness, use and perceived effectiveness in smoking cessation among Chinese daily smokers in Hong Kong. METHODS: Daily smokers (N = 1,307) were recruited to a community-based randomised controlled trial (‘Quit to Win’) in 2014. Socio-demographic characteristics, conventional cigarette smoking status, nicotine addiction level, quit attempts, quit intention, e-cigarette awareness, use and perceived effectiveness on quitting were reported at baseline and 1-week follow-up. Multivariate logistic regression was used to identify factors associated with e-cigarette awareness, use and perceived effectiveness in quitting. RESULTS: Most smokers (82.6%, 95% CI 80.2%-84.9%) had heard about e-cigarettes, and 13.3% (11.3%-15.5%) ever used e-cigarettes. Most users (74.1%) and non-users (91.2%) did not perceive e-cigarettes as effective in quitting. Being younger and having a larger family income were associated with e-cigarette awareness. Being younger, a tertiary education and a stronger addiction to nicotine were associated with e-cigarette use, which was itself associated with lower levels of intention to quit and had no association with attempts to quit (P for trend 0.45). E-cigarette use, the last quit attempt being a month earlier, having made a quit attempt lasting 24 hours or longer and perceiving quitting as important were all associated with the perceived effectiveness of e-cigarettes in quitting (all P <0.05). CONCLUSIONS: Among community-recruited smokers who intended to quit, awareness of e-cigarettes was high, but most did not perceive e-cigarettes as effective in quitting. Correlates concerning e-cigarette perceptions and use will help to inform prospective studies, public education and policy on controlling e-cigarettes.